International collaboration in digital knowledge work: A production-side assessment of Europe's digital single market - Lena Abou El-Komboz; Moritz Goldbeck (EconPol Forum, 2024)
Low market integration is a major barrier to European competitiveness in the digital economy. International collaboration of knowledge workers could help to harness market size advantage. Data from the largest coding platform reveals digital collaboration in Europe drops by 16.4 percent at borders. This border effect is 73 percent larger than between US states. Organizations and cultural proximity facilitate international collaboration. European digital single market policymaking should address production-side barriers to support the digital economy.
Keywords: 330